Life and death in The Seventh Seal. Reflections from a hermeneutical perspective - García Durán, Arantza Monserra (2025)
The essay below is a hermeneutical reflection that seeks to reach interpretations about the symbolic meaning manifest in the film “The Seventh Seal” by filmmaker Ingmar Bergman. There is no intention to impose a single interpretation, but rather a way of seeing cinema as a piece of art that provides aesthetic and philosophical references. The intention as well is to recognize the point of awareness in which we immerse ourselves when watching this film in relation to the experience of our own realities.